Role of miR-27a in the regulation of cellular function via the inhibition of MAP2K4 in patients with asthma. (December 2021) - Yang, W; Wang, Z; Luo, L; Yang, P; Sun, D; Gao, B
Asthma is a respiratory disease with a clinically high incidence, and repeated attacks of asthma severely affect the quality of life and even pose a threat to health, leading to severe burdens on families and even the society. A thorough understanding of the pathogenesis of asthma is essential for the prevention and treatment of asthma. This study aimed to examine the effect of the microRNA miR-27a on asthma and its relationship with mitogen activated protein kinase 4 (MAP2K4). Patients with asthma admitted to our hospital from August 2016 to August 2018 and healthy participants in the same period were included in this prospective analysis. The mRNA expression levels of miR-27a and MAP2K4 in peripheral blood were determined. Airway smooth muscle cells (ASMCs) were used to study the effects of miR-27a and MAP2K4 on cell biological behavior. The relationship between miR-27a and MAP2K4 was verified using dual-luciferase reporter assay. miR-27a expression was increased and MAP2K4 mRNA expression was decreased in asthma (P < 0.05). Increasing miR-27a expression and inhibiting MAP2K4 expression could enhance the activity of ASMCs, whereas inhibiting miR-27a expression and increasing MAP2K4 expression had the opposite effect (P < 0.05). Dual-luciferase reporter assay results showed that the fluorescence activity of MAP2K4-wild type was inhibited by increased miR-27a expression (P < 0.05). miR-27a promotes the proliferation and invasion of ASMCs by targeting MAP2K4 and is involved in the occurrence of asthma.